English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve The following system by elimination

–x + 3y = 6
x – 9y = 9

2007-04-23 14:06:35 · 6 answers · asked by Crazyhorse 1 in Science & Mathematics Mathematics

6 answers

add the equations

-6y = 15
divide by -6
y = -5/2

plug into either of the original equations
-x + 3(-5/2) = 6
-x = 6 + 15/2
-x = 27/2
divide by -1
x = -27/2

2007-04-23 14:12:23 · answer #1 · answered by dewkisses02 4 · 0 0

Add; -6y = 15; y = 15/-6 = -5/2

-x + 3y = 6; -x + 3(-5/2) = 6
-x - 15/2 = 6; -x = 27/2; x = -27/2

2007-04-23 21:11:46 · answer #2 · answered by richardwptljc 6 · 0 0

It's pretty much set up for you
-x+3y=6
+ x-9y=9
The x's cancel out and then u just add the like terms

-6y=15
divide by -6

y=-2.5

2007-04-23 21:12:11 · answer #3 · answered by Donald 2 · 0 0

The quickest elimnation to add the equations together to get - 6y = 15, or y = -5/2. Then substitute back into either equation to find x.

2007-04-23 21:11:39 · answer #4 · answered by cattbarf 7 · 0 0

–x + 3y = 6
x – 9y = 9
---------------------
-6y = 15
y = -5/2

x - 9(-5/2) = 9
x + 45/2 = 9
x = -27/2

(-27/2 , -5/2)

2007-04-23 21:11:18 · answer #5 · answered by      7 · 0 0

since the signs are different u add
-6y= 15
y= -15/6
y = -2.5

2007-04-23 21:13:14 · answer #6 · answered by jay gal 3 · 0 0

fedest.com, questions and answers